(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
As world practice shows, not a single great power can achieve success without allies. A country that aspires to become a power seeks to achieve its goal by relying on its allies. Turkey is one of the powerful countries that wants to become a world power and does not have enough resources for this. Therefore, at present, the problem of a thorough study of Turkey’s foreign policy, signs of neo-imperialism (neo-Ottomanism), pan-Turkism and pan-Islamism in it is urgent. The relevance of the topic is characterized by the growing role of Turkey in foreign policy and competition with the main players in geopolitics. The article presents a conceptual analysis of the foreign policy of modern Turkey from 2002 to the present. Particular attention was paid to Turkey’s influence in the countries of Central Asia, the Balkan Peninsula, the Middle East and Africa, namely the problems and opportunities in the geopolitical struggle, as well as Turkey’s relations with the United States of America and the Russian Federation.